2022
DOI: 10.1002/ejsp.2882
|View full text |Cite
|
Sign up to set email alerts
|

What should allies do? Identifying activist perspectives on the role of white allies in the struggle for racial justice in the United States

Abstract: http://sro.sussex.ac.uk Selvanathan, Hema Preya, Ulug, Ozden Melis and Burrows, Brooke (2022) What should allies do? Identifying activist perspectives on the role of white allies in the struggle for racial justice in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…As the minority group’s conflict narrative frames the Turkish-Kurdish conflict as an independence problem for Kurds, even though allies in general support minority rights, strong allies may have different preferences to support Kurds compared to weak allies. One study has shown that allies have different positions on what their role as allies to disadvantaged group members should be (Selvanathan et al, 2020b). We believe that Turkish allies also have different positions on how to support Kurds in the Turkish-Kurdish conflict context (e.g., from supporting language rights to supporting an independent Kurdistan).…”
Section: Discussionmentioning
confidence: 99%
“…As the minority group’s conflict narrative frames the Turkish-Kurdish conflict as an independence problem for Kurds, even though allies in general support minority rights, strong allies may have different preferences to support Kurds compared to weak allies. One study has shown that allies have different positions on what their role as allies to disadvantaged group members should be (Selvanathan et al, 2020b). We believe that Turkish allies also have different positions on how to support Kurds in the Turkish-Kurdish conflict context (e.g., from supporting language rights to supporting an independent Kurdistan).…”
Section: Discussionmentioning
confidence: 99%
“…Students' negative perceptions toward faculty members' commitment and accountability reflected recurring concerns about aspiring allies (Droogendyk et al, 2016). In addition, the Feedback sign's wording suggested that Black students should bear the responsibility of educating faculty members how to be an ally to Black students and allow faculty members to relinquish accountability for their learning, a common faux pas of aspiring allies (Selvanathan et al, 2023). Though this was not the intent of the Feedback sign, its impact on some students is nonetheless valid.…”
Section: Resultsmentioning
confidence: 99%
“…We then placed our findings in conversation with relevant existing literature. Grounded theory is an analytical approach that examines processes, actions, and interactions (Glaser & Strauss, 1967;Savin-Baden & Major, 2013). An aim of grounded theory is to yield novel understandings "through an interactive process that involves the creation and refinement of abstract conceptualizations of particular phenomena" (Jones et al, 2014, p. 77) versus extrapolating an existing theoretical framework onto participants' experiences (Glaser & Strauss, 1967).…”
Section: The Current Studymentioning
confidence: 99%
“…We are asking social psychologists to reorient the field away from individualism and to think about how we are in connection with each other; to change structures that demand and provide individual solutions because systemic change is too heavy a price for hegemonic psychology to pay. This process also involves recognizing and working through the tensions that manifest when building solidarity between groups of people with varying levels of privilege (Nadesan, 2019 ; Selvanathan et al, 2022 ). It requires us to rethink the pace in which knowledge is expected to be produced and recognize how disabled and Otherised scholars are often left in the wake of this academic culture of/on speed (Lau, 2019 ).…”
Section: Reorienting Social Psychologymentioning
confidence: 99%